O papel da Educação Física na perspectiva dos discentes de uma Escola Estadual de Tocantinópolis - TO - Silva, Raires da Costa (Universidade Federal do Tocantins, 2020)
The present study sought to understand the student perspective on the role of Physical Education in the school context. Verifying the tastes and the importance that the students attributed in the activities developed in the Physical Education classes. And from this, it was possible to analyze the characteristics of the subject compared to the other curricular components, and discuss how is the relationship teacher and student in the process of teaching / learning in Physical Education classes. The methodology used was the qualitative exploratory approach, the study was developed in astate school in Tocantinópolis-TO, the data collection instruments used was a questionnaire with an open question and focus group. Through the results obtained, the students 'perspective regarding the role of Physical Education in the school context was evidenced, thus allowing to reflect on the teacher / student relationship, and the students' view of the subject both positively and negatively in the school context.